METHODOLOGY FOR DESIGNING AN EXTERNAL CYLINDRICAL GRINDING CYCLE WITH AXIAL TRANSMISSION AND ANALYSIS OF DESIGN METHODS FOR POLISHING SCHEMES - Akramova Dilafruz Shuxrat qizi; Akramova Komila Shuxrat qizi (Journals Park Publishing, 2022)
The operations of circular external grinding with axial feed, performed on CNC machines, are widely used in mechanical engineering. In this article, we reviewed the methodology for designing an external cylindrical grinding cycle with axial transmission, and also made an analysis of the methods for designing polishing schemes on machine tools.
Keywords: Grinding; circular polishing; axial transmission